Aplicaciones del marco DigCompEdu en la formación de docentes de secundaria. Una revisión sistemática de la literatura (Memorias Sifored - Encuentros Educación UAN, 2023)
The design of curricular proposals for training in digital teacher competencies requires constant updating from global references that comprehensively address the aforementioned competencies. This systematic literature review aims to identify the influence of the DigCompEdu framework in the design of training proposals and diagnostic evaluation of the digital competencies of secondary school teachers between 2017 and October 2022. The parameters of the PRISMA methodology were followed based on a database product of the SCOPUS analysis of completed articles published in English, Portuguese and Spanish. The final sample (n=29) was analyzed in depth with Atlas.ti. It was identified that the DigCompEdu framework of the European Commission is the main reference in this type of training, face-to-face or virtual. In addition, it is highlighted that Spain and Portugal lead the design and application of ad hoc or previously validated diagnostic research based on this framework, and that the trend is to develop teaching competence comprehensively with the six areas of DigCompEdu with permanent communication channels, present not only during training.
Keywords: Teacher education; secondary education; technological education; educational research; systematic review